The role of non-financial incentives in B2B sales force motivation : A case study of a Finnish technology consulting company - Rentola, Matias (My University, 2018)
Sales professionals operate in an environment susceptible to market fluctuations and internal and external pressure from clients and the organization. Thus, it is crucial to understand what motivates and drives the individuals of a sales force is vital in determining company success in the long-run. More importantly, as financial incentives are the norm in 21st century sales organizations, it is important to understand how sales professionals are motivated and retained through non-financial incentives. The purpose of this study is to investigate the role of non-financial incentives in B2B sales force motivation. The research sheds light to this phenomenon through studying what non-financial incentives are used in motivating the sales force and, how non-financial incentives have motivational value to employees. The theoretical framework of the study is constructed through presenting and discussing the current state of knowledge of motivation, sales people as a workplace demographic. and employee incentives. First, a wide range of motivation theories is discussed with the focus on content and process theories of motivation. Second, the specific characteristics of motivating sales people and their personality types are analyzed. Third, employee incentives are discussed to create a wide understanding of the targets of motivation, their specifics, and motivation as a phenomenon. This study was done as a single-case study using qualitative methods and focusing on one Finnish technology consulting company. More specifically, the sales force consisting of four individuals was at the focal point of the data collection. The main data collection was done through four interviews with individuals from the case company’s sales force. The study supports the theoretical framework to a large extent. However, there are a few distinct notions which should be taken into account in the theoretical discussion, but also managerially. First, the widely accepted notion that sales people tend to favor financial incentives over non-financial incentives is not supported by this study. According to the findings non-financial incentives such as freedom, learning and the work itself seem to be of great importance to the case company sales people. Also, managers should take into account the fact that not all motivation is equally valuable. Non-financial incentives seem to drive motivation on a longer time period and more profoundly than financial incentives.
Keywords: motivation, B2B Sales, non-financial incentives, financial incentives